The Effect of Capital Expenditure, Growth Opportunity, Investment Opportunity Set and Dividend Policy on Firm Value - Pradhika Karina Putri; Shella Segara (Yayasan Az Zukhruf Cendikia, 2025)
Purpose – This study aims to obtain empirical evidence on the influence of Capital Expenditure, Growth Opportunity, Investment Opportunity Set and Dividend Policy on Firm Value Design/methodology/approach – This study uses quantitative data, and the sample size is quantitative. The sample comprises 79 companies in the industrial and basic materials sectors listed on the Indonesia Stock Exchange between 2022 and 2024. The analysis technique used to test the hypotheses is multiple regression analysis using Eviews 9 software. Findings – The results of this study indicate that capital expenditure has no effect on firm value, growth opportunities have no effect on firm value, investment opportunities have an effect on firm value, and dividend policy has no negative impact on firm value. Research limitations/implications – The data used is secondary data obtained from company annual reports, but there are several companies that do not publish annual reports. The dividend per share figures for 2024 are listed in the 2025 annual report, which has not yet been published. This study has limitations in terms of sample size; out of a total of 177 companies, only 79 companies met the sample criteria. JEL : G31, G32, G35